2016
DOI: 10.1161/strokeaha.116.014794
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Early and Delayed Cerebral Infarction After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Cerebral infarction after aneurysmal subarachnoid hemorrhage is a significant cause of substantial morbidity and mortality. Because early and delayed cerebral infarction after aneurysmal subarachnoid hemorrhage may be mediated by different processes, we evaluated whether aneurysm-securing methods contributed to infarcts and whether long-term outcomes differ between early and delayed infarcts. Methods-A post hoc analysis of the CONSCIOUS-1 study (Clazosentan to Overcome Neurological Ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…On review of the literature, previous large-scale studies examining the incidence of cerebral infarction after aSAH (defined as hypodensities visualized on CT images) observed a putative infarction rate during admission ranging from 29.8% to 61.3% (mean 44.0%, n = 4), 4,12,14,21 with a mean rate among surgically treated patients of 44.7% (SD 14.2%). In addition, similar to our study, the rate of postprocedural infarction was typically higher among patients treated with clipping, 4,14,21 with 1 exception.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On review of the literature, previous large-scale studies examining the incidence of cerebral infarction after aSAH (defined as hypodensities visualized on CT images) observed a putative infarction rate during admission ranging from 29.8% to 61.3% (mean 44.0%, n = 4), 4,12,14,21 with a mean rate among surgically treated patients of 44.7% (SD 14.2%). In addition, similar to our study, the rate of postprocedural infarction was typically higher among patients treated with clipping, 4,14,21 with 1 exception.…”
Section: Discussionmentioning
confidence: 97%
“…The cutoff of 10 ml 3 was chosen on the basis of previous work suggesting that infarctions of this size are associated with poor functional outcome after clipping of ruptured aneurysms. 4 Hypodensity volumes were determined using the xyz/2 method, with x, y, and z representing the maximal dimensions of the infarct in 3 orthogonal planes. and range, and as frequency and percentage, respectively.…”
Section: Patient Characteristics and Covariates Of Interestmentioning
confidence: 99%
“…Delayed cerebral ischemia usually occurs within two weeks of aSAH and is a common and severe complication of aSAH. The results of medicinal treatment for DCI are often not satisfactory, and it usually leads to permanent damage to neurological functions, resulting in disability or even death of SAH patients(Al-Mufti et al, 2019;Ayling, Ibrahim, Alotaibi, Gooderham, & Macdonald, 2016;Budohoski et al, 2012;Macdonald, 2014;Ostergaard et al, 2013).If early prognosis of the risk of DCI could be achieved, optimized care and improved allocation of healthcare resources might be facilitated. Although qualitative or semiquantitative clinical grades (such as WFNS grade and modified Fisher grade) are well known…”
mentioning
confidence: 99%
“…Tsyben et al (17) reported 2 patients with delayed ischemic deficit due to vasospasm after non-ruptured aneurysm surgery. Clipping is an independent risk factor for the development of early cerebral infarcts, whereas delayed cerebral infarcts are associated with angiographic vasospasm (18). In a study dealing with the prevention of vasospasm, Kawahara et al (19) recommended to perform early lumbar drainage in patients with SAH.…”
Section: Discussionmentioning
confidence: 99%